Notice of Removal: PIC simulation study of dielectric-filled S-band magnetically insulated line oscillator (MILO) - Kumar A.; Tripathi P.; Dwivedi S.; Jain P.K. (My University, 2025)
In this paper, S-band dielectric-filled magnetically insulated line oscillator (MILO) has been designed and simulation has been performed using 3D PIC code 'CST'. The dielectric-filled MILO is a new kind of HPM device having slow wave structure partially filled with low-loss dielectric to enhance the overall efficiency. The device design methodology follow the similar step of conventional MILO. To validate the designed structure, beam-absent simulation performed using Eigenmode solver to find dispersion curve. Finally, with the beam parameters: 600 kV voltage and 45 kA current, a high power microwave of \pmb{\sim 4} GW peak power at 2.57 GHz frequency generated in TMm mode. The efficiency of the device obtained is 14.8%. © 2019 IEEE.